“What Would You Do In My Place?” Outcomes of a Collaborative Health Literacy Research Study in Rural Nova Scotia - B. Allan Quigley (Adult Education Research Conference, 2004)
The 1994 and 2000 International Adult Literacy Surveys found that 43% of Canada’s adult population is affected by low literacy skills, with 22% of these adults experiencing severe literacy problems. The highest rates of low-literacy skills have consistently been found in the Atlantic provinces. However, what these studies do not reveal are the life-and-death health issues that often lie beneath the statistics. To the question: “What would you do in my place?” posed to us by an unemployed fish plant worker with low literacy skills and severe health issues living in an isolated Nova Scotia community, such surveys provide no answers. This two-year study investigated: 1) factors that influence ways less literate adults in NE Nova Scotia access and act upon health information and services, and 2) strategies for change that could build on capacities for achieving health.